Oscillatory pallidal local field potential activity correlates with involuntary EMG in dystonia. - Chen, C; Kühn, A; Hoffmann, K; Kupsch, A; Schneider, G; Trottenberg, T; Krauss, J; Wöhrle, J; Bardinet, E; Yelnik, J; Brown, P (2006)
The pathophysiology of dystonia is unclear. The authors recorded local field potentials (LFPs) from deep brain stimulation electrodes implanted in the pallidum of 13 dystonic patients. LFP power correlated with the level of dystonic EMG in the sternocleidomastoid, with maximal positive correlations at the lower contacts of pallidal electrodes. The data suggest that the neuronal synchronization indexed by LFP oscillations in the globus pallidus may be mechanistically linked to dystonic EMG activity.